Survival Outcomes and Epidemiological Characteristics of Pediatric Leukemia: A Retrospective Cohort Study from a Tertiary Cancer Center in Western India (GAIMS Journal of Medical Sciences, 2026)
BackgroundLeukemia represents the most common malignancy among children worldwide and contributes substantially to pediatric cancer mortality, particularly in low- and middle-income countries. Survival outcomes vary widely depending on disease subtype, treatment availability, and healthcare resources.ObjectivesTo evaluate the epidemiological characteristics and survival outcomes of pediatric leukemia patients treated at a tertiary care cancer center in Western India.Materials & MethodsA retrospective cohort study was conducted at the Gujarat Cancer and Research Institute (GCRI), Ahmedabad. Pediatric patients aged ≤18 years diagnosed with leukemia in the year 2019 were included and followed up for the period of five years till December 2024. Data were extracted from hospital-based cancer registry records and medical case files. Kaplan–Meier survival analysis was used to estimate overall survival, and regression analysis was performed to identify factors associated with mortality.ResultsA total of 424 pediatric leukemia patients were included in the study. The cohort comprised 65.6% males and 34.4% females, with a mean age at diagnosis of approximately 8.5 years. Acute lymphoblastic leukemia (ALL) was the most common subtype (77.4%), followed by acute myeloid leukemia (AML) (17%) and chronic myeloid leukemia (CML) (5.7%). The five-year overall survival proportion was 46.2%. Kaplan–Meier analysis demonstrated significant differences in survival according to leukemia subtype (p